2015
DOI: 10.1039/c5ra10374f
|View full text |Cite
|
Sign up to set email alerts
|

Morphology controlled growth of ZnAl-layered double hydroxide and ZnO nanorod hybrid nanostructures by solution method

Abstract: Morphological evolution of ZnAl-based hybrid nanostructures from ZnAl layered double hydroxide to ZnO nanorods grown by a hydrothermal method depending on the thickness of the Al2O3/ZnO double seed layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The lattice fringe spacing of the crystallite in Figure 2b was calculated to be 0.20 nm (Figure 2c,d). This value corresponds to the 018 planes of the LDH, 36,37 which demonstrated that the LDH with a lateral size of less than 10 nm was successfully obtained. The lattice fringe spacing of the crystalline in the other circled area in Figure 2b was also calculated to be 0.20 nm (Figure S2).…”
Section: Methodsmentioning
confidence: 79%
“…The lattice fringe spacing of the crystallite in Figure 2b was calculated to be 0.20 nm (Figure 2c,d). This value corresponds to the 018 planes of the LDH, 36,37 which demonstrated that the LDH with a lateral size of less than 10 nm was successfully obtained. The lattice fringe spacing of the crystalline in the other circled area in Figure 2b was also calculated to be 0.20 nm (Figure S2).…”
Section: Methodsmentioning
confidence: 79%
“…This is because of the difference in the Zn 2+ /Al 3+ ratio depending on the synthesis condition. Because the ionic radii of Al 3+ (0.675 nm) is smaller than that of Zn 2+ (0.88 nm), the interplanar distance can change with a variation in the Zn 2+ /Al 3+ ratio. , The Al 3+ was supplied only by the Al thin film, while the Zn 2+ was sufficiently supplied by the solution even after the dissolved Al depleted. Therefore, Zn 2+ occupies a larger proportion in the lattice than Al 3+ does.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of LDHs can be modulated by combination with a wide variety of metal cations and anions. Among them, ZnAl-LDH is an excellent visible-blind UV-absorbing material because of its wide band gap, easy fabrication by low-temperature hydrothermal synthesis, low cost, and environmental friendliness. Particularly, because of the advantages of multiple sheets structure, that is, a scroll structure, it exhibits excellent flexibility or bendability. In this paper, we demonstrate for the first time the feasibility of using an LDH nanosheet with a scroll structure as an active layer in a flexible and visible-blind UV photodetector (Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Gaini et al reported Mg-Al-CO 3 −2 for the de-coloration of indigo carmine6. Panda et al reported Mg/Al-LDH and study its various factor on its growth such as various metal cation concentration, pH and aging time22. Similarly, Shao et al investigated ZnTi-LDH by co-precipitation methods for the de-coloration of methylene blue dyes under the influence of visible light irradiation23.…”
mentioning
confidence: 99%
“…Similarly, Shao et al investigated ZnTi-LDH by co-precipitation methods for the de-coloration of methylene blue dyes under the influence of visible light irradiation23. The ZnAl-LDH was synthesized by Beak et al through hydrothermal methods22. Beside metal-metal combination the LDH was supported on various support to increase its catalytic performance.…”
mentioning
confidence: 99%